A new karst-obligate species of the genus Pinellia (Araceae) from Guangxi, China - Ma, Zhengxu; Li, Yifan (Phytotaxa, 2025)
A new aroid species, Pinellia calcicola, from the South China Karst in northern Guangxi, is described and illustrated. The species is diagnosed against P. cordata and P. polyphylla, and is recognized by a tuberous and karst-obligate lithophytic habit, an epigeal and superimposed bulbil developed at the apex of the petiolar sheath, a broadly sagittate leaf blade with posterior lobes that acuminate and mucronate at the apex, and an erect and sub-boat-shaped spathe limb, becoming flattened during anthesis. A revised key to the Pinellia species with entire leaves is also provided. Additional specimens of this new species were examined and collected for the Fourth National Survey of Chinese Materia Medica.